Surgical techniques in orthopaedics minimal incision total hip arthroplasty - Stuchin, Steven A.; American Academy of Orthopaedic Surgeons (Rosemont, Ill. : American Academy of Orthopaedic Surgeons, 2003)
(Producer) Achieve superior clinical performance of total hip arthroplasty, while minimizing surgical trauma, tissue dissection, and scarring, Focusing on minimal incision aproaches, learn how an exposure with more retraction may be achieved using a smaller incision, resulting in improved cosmesis, less perioperative pain, and a shorter hospital stay
Approved for a maximum of three category 1 credits toward the AMA Physician's Recognition Award
DVD
Keywords: Arthroplasty, Replacement, Hip -- methods